Implementasi Google Drive Sebagai Alternatif Perpustakaan Digital Di Perpustakaan Program Studi Ilmu Pemerintahan Universitas Islam Negeri Sultan Thaha Saifuddin Jambi - Hidayati, Hidayati; Raudhoh, Raudhoh; Yusufhin, Fridinanti (Program Studi Ilmu Perpustakaan dan Informasi Fakultas Adab dan Humaniora UIN Sulthan Thaha Saifuddin Jambi, 2022)
ABSTRACT Introduction. This research intends to simplify and speed up the process of developing a conventional library of government science study programs and increasing the diversity of collections in digital form. The implementation of e-governance in the library field begins with the use of cloud computing by using Google Drive, users can get references easily and quickly. Google drive was chosen because it is easy to use and understand by lay people who do not have a librarian background because the Government Science study program does not have a librarian. Data Collection Methods. This study uses a qualitative method with a descriptive approach. Starting from observation, interviews to documentation. Data Analysis. Data analysis uses reduction, data presentation and conclusion drawing. Results and Discussion. The application of Google Drive as an alternative to digital libraries in the Government Science study program library, consists of several work systems such as contributors, admins, and users. There are obstacles such as copyright, user education, scanner, service, content, budget, and e-books in foreign languages. The advantages are low cost, easy to implement and information preservation, while the disadvantages are less efficient access systems and internet connections. Conclusion. The application of Google Drive as an alternative to digital libraries in the Government Science study program library, consists of several work systems such as contributors, admins, and users. There are obstacles such as copyright, user education, scanner, service, content, budget, and e-books in foreign languages. The advantages are low cost, easy to implement and information preservation, while the disadvantages are less efficient access systems and internet connections.